Medical slang in Rio de Janeiro, Brazil Trambiclínicas, pilantrópicos, e mulambulatórios - Christopher Peterson (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
The author analyzes medical slang in Rio de Janeiro based on the view of interactive or live metaphor proposed by such authors as Black and Ricoeur, applied to puns and other jokes from medical work, with the goal of unveiling what physicians mean by this linguistic register. The article classifies medical slang in three broad areas, pertaining to the physician's relations with professional training and knowledge, patients, and health care services. Comparing his empirical material with previous studies focusing on hospital slang for patients, the author identifies, in addition, a range of slang terms for health care services themselves. The article points to interfaces between medical slang and the Brazilian "health hypercrisis" identified by Schramm. O autor analisa a gíria médica carioca a partir da visão de metáfora interativa ou viva proposta por autores como Black e Ricoeur, aplicada a trocadilhos e outros chistes do cotidiano médico, com o objetivo de desvendar o que os médicos significam ou "querem dizer" com esse registro lingüístico. O artigo adota uma classificação da gíria em três áreas temáticas, i.é., na relação do médico com a formação profissional, com os pacientes e com os serviços de saúde. Comparando seu material empírico com o de estudos americanos que enfocam chistes para pacientes, o autor identifica, além destes, uma série de trocadilhos para os próprios serviços de saúde, levando-o a sugerir interfaces entre a gíria médica e a "hipercrise sanitária" identificada por Schramm.